Contextualizing Islamic Law Through Istihsan: An Analysis of Customary Inheritance Practices in Air Nipis Sub-District, South Bengkulu - Iim Fahimah; Mualimin Mochammad Sahid; Toha Anis Malik; Zurifah Nurdin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study analyzes the practice of customary inheritance in Air Nipis District, South Bengkulu, using the istihsan approach in Islamic law. The research uses a qualitative method with a descriptive-analytical approach, collecting data through in-depth interviews and direct observation of customary leaders, inheritance law experts, and community members involved in inheritance distribution. The results show that the traditional inheritance system in Air Nipis prioritizes family welfare by considering the roles and responsibilities of heirs, particularly those who care for the deceased, although this sometimes leads to uneven distribution. The contextualization of Islamic law in this practice can be understood through the concept of istihsan, which provides flexibility in applying inheritance rules to align with the social conditions and needs of the family. Istihsan allows deviations from rigid inheritance provisions when there are strong reasons that support justice and benefit within the family. This study offers insights into how istihsan can be an inclusive and responsive approach to customary inheritance practices while maintaining a balance between legal norms and social needs.